2018
DOI: 10.1177/0361198118793499
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of Change in Posted Speed Limit from 65 to 70 mph on Rural Virginia Interstate System

Abstract: Effective July 1, 2010, the Virginia Department of Transportation (VDOT) increased the maximum posted speed limit on interstates and similar facilities from 65 to 70 mph, if recommended following an engineering study. As a result, VDOT performed engineering studies on selected rural interstates posted at 65 mph. By November 2010, VDOT had increased the speed limit from 65 to 70 mph for approximately 670 centerline miles of select rural interstates. This paper presents the results of an empirical Bayes before–a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, the recent increase in regulatory speed limit to 75 mph on 600 mi of freeway in Michigan raises concerns on traffic safety and operations at these locations. Since the repeal of the 1974 NMSL, the majority of studies found that crash frequency and the number of fatalities increased as a result of speed limit increase (18)(19)(20)(21)(22). Research has shown speed limit increases to be associated with adverse impacts on the roadways where the limits were, as well as adjacent facilities or across the road network as a whole (4,23).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the recent increase in regulatory speed limit to 75 mph on 600 mi of freeway in Michigan raises concerns on traffic safety and operations at these locations. Since the repeal of the 1974 NMSL, the majority of studies found that crash frequency and the number of fatalities increased as a result of speed limit increase (18)(19)(20)(21)(22). Research has shown speed limit increases to be associated with adverse impacts on the roadways where the limits were, as well as adjacent facilities or across the road network as a whole (4,23).…”
Section: Literature Reviewmentioning
confidence: 99%